Developing SOA-enabled service agility capabilities: case studies in services industry. (2018) - Raman, Aparna; Bharadwaj, Sangeeta Shah; Mukherjee, Jaydeep
The research paper explores how information technology, specifically service-oriented architecture (SOA)-enabled service agility capabilities, were developed. The paper defines the service agility capabilities (sensing and responding) using dynamic capabilities theory and service dominant logic. In this research, we present two case studies, based on the services sector. This paper explains, 'how' these capabilities were developed by responding organisations. Based on the research results, the propositions were proposed. Further, the model was supported through thematic analysis. The study contributes towards the knowledge base of agility and reveals how SOA-enabled capabilities are developed to achieve agile services.